Feasibility Analysis of Subject Specific Pedagogy Physics Learning Module Based on Project Based Learning Integrated with Merdeka Curriculum on Alternative Energy Material - Muhtar Husnadi; Sri Budiawanti; Elvin Yusliana Ekawati (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to analyse the feasibility of Subject Specific Pedagogy Physics tools based on Project Based Learning (PjBL) integrated with Merdeka Curriculum on alternative energy material for grade X high school students. This research uses the Research and Development (RnD) method with the 5D model (Define, Design, Develop, Disseminate, and Evaluate) which is limited to the devalope stage. The Define stage includes needs analysis and identification of competencies that must be achieved by students. The Design stage includes designing learning module in the form of modules and student worksheets. The Develop stage includes the development and validation of learning modules by experts in the aspects of material, learning, language and limited testing. The results showed that the PjBL-based Physics Subject Specific Pedagogy device integrated with the Merdeka Curriculum on alternative energy material for grade X high school students had high feasibility based on expert review in terms of material, learning, and language aspects. In addition, students also gave positive responses to the developed learning module. Therefore, the learning module is suitable for use in the Physics learning process in high school.